2016
DOI: 10.1002/erv.2476
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Avoidant/Restrictive Food Intake Disorder in a Cohort of Adult Patients

Abstract: Adult patients with ARFID in this study were clinically distinct from those with AN and somewhat different from paediatric patients with ARFID in previous studies. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 13 publications
0
41
1
1
Order By: Relevance
“…In contrast to previous literature (Bryson et al, ; Nakai et al, ; Nicely et al, ; Norris et al, ; Strandjord et al, ), the average %mBMI of individuals with ARFID in our study was within the normal range, and was higher than %mBMI for AN. This is distinct from previous studies comparing these disorders, which have reported higher weights for those with ARFID relative to AN, but still found that individuals with ARFID were, on average, within an objectively low‐weight range (e.g., Fisher et al, ; Ornstein et al, ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous literature (Bryson et al, ; Nakai et al, ; Nicely et al, ; Norris et al, ; Strandjord et al, ), the average %mBMI of individuals with ARFID in our study was within the normal range, and was higher than %mBMI for AN. This is distinct from previous studies comparing these disorders, which have reported higher weights for those with ARFID relative to AN, but still found that individuals with ARFID were, on average, within an objectively low‐weight range (e.g., Fisher et al, ; Ornstein et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…This is distinct from previous studies comparing these disorders, which have reported higher weights for those with ARFID relative to AN, but still found that individuals with ARFID were, on average, within an objectively low‐weight range (e.g., Fisher et al, ; Ornstein et al, ). Many of the published chart reviews on ARFID retrospectively classified individuals who had been evaluated before the inclusion of ARFID in the DSM‐5 (e.g., Nakai et al, ; Nicely et al, ; Norris et al, ; Ornstein et al, ). It is possible that individuals with certain presentations of ARFID, such as significant weight loss or reliance on enteral feeding, presented or were referred to eating‐disorder programs because of complications related to low‐weight, and that those with other forms of ARFID (e.g., those with nutritional deficiencies) were not captured in earlier comparison studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a series of case reviews and clinical studies across eating disorder treatment programs in North America found that between 7.2% and 17.4% of patients across sites had ARFID 4,5,6 In a similar retrospective chart review of individuals seeking treatment for eating disorders in Japan, 11% met criteria for ARFID. 7 Further, ARFID was even more common (22.5%) among youth in a day treatment program for eating disorders. 8 By contrast, a retrospective review of 2,231 consecutive referrals (aged 8–18 years) to pediatric gastrointestinal clinics in the Boston area showed an ARFID prevalence of only 1.5%.…”
Section: What Is Currently Known?mentioning
confidence: 96%
“…Overall, patients with ARFID tend to be younger than patients with other eating disorders and the reported gender proportions among them are less skewed towards female gender, although girls or women still make up a majority of patients. An exception is the study by Nakai et al (2016), in which all ARFID patients were female.…”
Section: Dsm-5 Criteriamentioning
confidence: 99%